Alice M. Rivlin papers - Rivlin, Alice M.
Correspondence, memoranda, speeches, writings, reports, congressional testimony, newspaper clippings, printed matter, photographs, and other papers pertaining to Rivlin's career as an economist and government official. Documents her association with the Brookings Institution and the institution's Economic Studies Program, her work at the Dept. of Health, Education, and Welfare (HEW) as assistant secretary for program coordination (1966-1968) and for planning and evaluation (1968-1969), and her directorship of the Congressional Budget Office (1975-1983). Topics include aging, civil rights movements, economy, education, federal budget and deficit, health, income maintenance programs, program budgeting, public welfare, social experimentation, social policy and research, and social unrest in the late 1960s.
Documents HEW staff reactions to recommendations on education issued by the National Advisory Commission on Civil Disorder (Kerner Commission), meetings between HEW officials and representatives of the Poor People's Campaign (1968), and the transition at HEW from the Lyndon B. Johnson to the Richard M. Nixon administrations. Also documents Rivlin's activities as a member of the boards of the Black Student Fund, Bryn Mawr College, and Harvard University, her participation in the National Longitudinal Study of the High School Class of 1972, her travels to China as a member of the Carnegie Council on Policy Studies in Higher Education, her work with the Ford Foundation's Project on Social Welfare and the American Future, National Research Council's Committee on Federal Agency Evaluation Research, National Conference on Social Welfare's Committee on Federalism and National Purpose, and Brookings Panel on Social Experimentation. Includes an "issues book" compiled by Rivlin for presidential candidate Edmund S. Muskie between 1970 and 1972.
Correspondents include Gardner Ackley, Daniel Bell, John Brademas, John Hope Franklin, Charles E. Fritz, John Kenneth Galbraith, Herbert J. Gans, Kermit Gordon, William Gorham, Walter W. Heller, Clark Kerr, Bruce King, Daniel P. Moynihan, Edmund S. Muskie, Joseph A. Pechman, William Proxmire, Charles S. Robb, Charles L. Schultze, Neil J. Smelser, Elmer B. Staats, James Wilfrid Vander Zanden, Paul A. Volcker, and Timothy E. Wirth.
Economist, government official, and director of the Congressional Budget Office (1975-1983). Born 1931.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ackley, Gardner -- Correspondence; Bell, Daniel, -- 1919-2011 -- Correspondence; Brademas, John, -- 1927- -- Correspondence; Franklin, John Hope, -- 1915-2009 -- Correspondence; Fritz, Charles E. -- Correspondence; Galbraith, John Kenneth, -- 1908-2006 -- Correspondence; Gans, Herbert J. -- Correspondence; Gordon, Kermit, -- 1916-1976 -- Correspondence; Gorham, William, -- 1930- -- Correspondence; Heller, Walter W. -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Kerr, Clark, -- 1911-2003 -- Correspondence; King, Bruce, -- 1924-2009 -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Muskie, Edmund S., -- 1914-1996.; Muskie, Edmund S., -- 1914-1996 -- Correspondence; Nixon, Richard M. -- 1913-1994.; Pechman, Joseph A., -- 1918- -- Correspondence; Proxmire, William -- Correspondence; Robb, Charles S. -- Correspondence; Schultze, Charles L. -- Correspondence; Smelser, Neil J. -- Correspondence; Staats, Elmer B., -- 1914-2011 -- Correspondence; Vander Zanden, James Wilfrid -- Correspondence; Volcker, Paul A. -- Correspondence; Wirth, Timothy E. -- Correspondence; United States. -- Congressional Budget Office; United States. -- Department of Health, Education, and Welfare. -- Office of the Assistant Secretary for Planning and Evaluation; United States. -- Department of Health, Education, and Welfare. -- Office of the Assistant Secretary for Program Coordination; United States. -- National Advisory Commission on Civil Disorders; Black Student Fund (U.S.); Brookings Institution; Brookings Panel on Social Experimentation; Bryn Mawr College; Carnegie Council on Policy Studies in Higher Education; Ford Foundation. -- Project on Social Welfare and the American Future; Harvard University; National Conference on Social Welfare; National Longitudinal Study of the High School Class of 1972.; National Research Council (U.S.). -- Committee on Federal Agency Evaluation Research; Aging; Budget -- United States; Budget deficits -- United States; Civil rights movements; Economics -- Study and teaching -- United States; Education -- United States; Health; High school students -- Longitudinal studies; Income maintenance programs; Poor People's Campaign; Presidents -- United States -- Election, 1972.; Public welfare -- United States; Social planning -- United States; China -- Description and travel; United States -- Economic conditions -- 1971-1981.; United States -- Economic conditions -- 1981-2001.; United States -- Economic policy -- 1971-1981.; United States -- Economic policy -- 1981-1993.; United States -- Politics and government -- 1945-1989.; United States -- Social conditions -- 1960-1980.